2021
DOI: 10.3390/antiox10050676
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds of Reynoutria sp. as Modulators of Oral Cavity Lactoperoxidase System

Abstract: Lactoperoxidase (LPO) together with its (pseudo)halogenation cycle substrates, H2O2 and thiocyanate ions oxidized to hypothiocyanite ions, form one of the main systems involved in antimicrobial defense within the oral cavity. In bacterial diseases such as dental caries, lactoperoxidase is oxidized to a form known as Compound II, which is characterized by its inability to oxidize SCN–, resulting in a decreased generation of antimicrobial products. Reynoutria sp. rizome extracts, due to their high polyphenol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that polyphenols exhibit antibacterial activity against the S. mutans (Figure 2, Table 2) [8,[41][42][43]. Babaeekhou and Ghane demonstrated that extracts of ginger have high antibacterial activity against S. mutans and S. sobrinus [44].…”
Section: Polyphenols and Dental Cariesmentioning
confidence: 99%
“…Numerous studies have shown that polyphenols exhibit antibacterial activity against the S. mutans (Figure 2, Table 2) [8,[41][42][43]. Babaeekhou and Ghane demonstrated that extracts of ginger have high antibacterial activity against S. mutans and S. sobrinus [44].…”
Section: Polyphenols and Dental Cariesmentioning
confidence: 99%
“…Recently, it became the spotlight of numerous studies, since its chemical composition has revealed promising therapeutic effects. Alcoholic, hydroalcoholic and water extracts from roots, rhizomes, and aerial parts (stems, leaves and flowers) have antibacterial activity [64,66,[93][94][95], antioxidant effects [44,58,66,[96][97][98][99][100][101][102][103][104][105], anticancer, antiproliferative and apoptotic properties [106][107][108], anti-inflammatory and antiviral activity [11,69,[109][110][111][112] and many other bioactive properties.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Magacz et al (2021) [95] proved the antibacterial effects of three Reynoutria species against Streptococcus mutans (S. mutans) and the positive impact on the prevention of caries formation. Due to the fact that extracts of the rhizomes of Reynoutria species are a rich source of polyphenols, they can balance the lactoperoxidase cycle, acting as activating/inhibiting agents for the antibacterial activity of the enzyme.…”
Section: Antibacterial Activitymentioning
confidence: 99%